Varenicline in the Treatment of Alcohol Use Disorders. (November 2014) - Erwin, Beth L.; Slaton, Rachel M.
Objective: To summarize the efficacy and safety data for the use of varenicline in the treatment of alcohol use disorders.Data Sources: A literature search was conducted in PubMed, International Pharmaceutical Abstracts, and Cochrane Library (through May 2014). Key search terms included varenicline, alcohol, alcohol dependence, alcoholism, ethanol, and nicotinic acetylcholine receptor . Additional references were identified from literature citations.Study Selection and Data Extraction: Results were limited to clinical trials and case reports that discussed either the use of varenicline in alcohol drinking patients or adverse effects experienced with its use. Only English language studies in humans were reviewed.Data Synthesis: In all, 7 randomized, placebo-controlled clinical trials and 1 open-label study were identified that evaluated the impact of varenicline on various drinking-related end points. The studies were conducted in patients dependent on alcohol (n = 4), non-alcohol-dependent patients (n = 3), and patients with a history of alcohol dependence but who had been abstinent for at least 6 months (n = 1). The majority of the studies classified their participants as heavy drinkers; however, this definition varied across studies. Most studies included smokers, but 2 trials included both smokers and nonsmokers.Conclusions: Evidence supports the use of varenicline for the reduction of alcohol craving as well as for the reduction of overall alcohol consumption in patients with alcohol use disorders. However, it is not likely to improve abstinence rates. Although most of the data were derived from patients with concurrent nicotine dependence, the effects of varenicline appear to occur independent of baseline smoking status.